ROLE AND POSITION OF THE DEFENDANT IN THE PLEA AGREEMENT - Sadriu, Vaxhid; Hajdari, Azem (Brawijaya Law Journal, 2019)
The object of this study is the plea agreement in the criminal procedure of Kosovo. The study focuses on defining the understanding of the plea agreement, specifying the role and position of defendant in the plea agreement, specifying the rights and obligations of the defendant in the plea agreement, and on the elaboration of the importance and effects of the plea agreement for the defendant and withdrawal of such agreement for the reasons that may be related to it. The results of this paper prove that the guilty plea agreement in the Kosovo courts practice has had a direct effect on mitigation the level of sentence or in some cases acquits punishment. Looking into this aspect, the biggest benefits resulted on favor of defendants with the status of cooperative witness. The contribution of this paper is theoretical and practical, since it deals with an issue almost untreated in Kosovo. These issues focus on legal solutions, theoretical approach, as well as operational aspects concretized in the practical activity of criminal procedure subjects. The legal, comparative, tracing and theoretical analysis methods have been helped in the preparation of this study.